An accurate position for the black hole candidate XTE J1752-223: re-interpretation of the VLBI data - Miller-Jones, James; Jonker, P.; Ratti, E.; Torres, M.; Brocksopp, C.; Yang, J.; Morrell, N. (Wiley-Blackwell Publishing Ltd., 2011)
Using high-precision astrometric optical observations from the Walter Baade Magellan Telescope in conjunction with high-resolution very long baseline interferometric (VLBI) radio imaging with the Very Long Baseline Array (VLBA), we have located the core of the X-ray binary system XTE J1752-223. Compact radio emission from the core was detected following the state transition from the soft to the hard X-ray state. Its position to the south-east of all previously detected jet components mandated a re-analysis of the existing VLBI data. Our analysis suggests that the outburst comprised at least two ejection events prior to 2010 February 26. No radio-emitting components were detected to the south-east of the core at any epoch, suggesting that the receding jets were Doppler-deboosted below our sensitivity limit. From the ratio of the brightness of the detected components to the measured upper limits for the receding ejecta, we constrain the jet speed ß > 0.66 and the inclination angle to the line of sight ? < 49°. Assuming that the initial ejection event occurred at the transition from the hard intermediate state to the soft intermediate state, an initial period of ballistic motion followed by a Sedov phase (i.e. self-similar adiabatic expansion) appears to fit the motion of the ejecta better than a uniform deceleration model. The accurate core location can provide a long time baseline for a future proper motion determination should the system show a second outburst, providing insights into the formation mechanism of the compact object.